Correction: A colorimetric probe for the real-time naked eye detection of cyanide and hydroxide ions in tap water: experimental and theoretical studies. Issue 1 (4th December 2019) - Uahengo, Veikko; Naimhwaka, Johannes; Daniel, Likius S.; Rahman, Ateeq; Elzagheid, Mohamed I.; Rhyman, Lydia; Ramasami, Ponnadurai; Cai, Ping
Abstract : Correction for 'A colorimetric probe for the real-time naked eye detection of cyanide and hydroxide ions in tap water: experimental and theoretical studies' by Veikko Uahengo et al., Analyst, 2019, 144, 6422–6431.